A Republic of Nobles. Studies in Polish History to 1864, ed. and transl. by J. Fedorowicz , coed. M. Bogucka and H. Samsonowicz - Russocki, Stanisław (Czasopismo Prawno-Historyczne, 1983)
Recenzja: A Republic of Nobles. Studies in Polish History to 1864, ed. and transl. by J. Fedorowicz, coed. M. Bogucka and H. Samsonowicz, Cambridge 1982, Cambridge University Press, ss. XVI, 293